1998
DOI: 10.1002/(sici)1097-0061(19980330)14:5<409::aid-yea237>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of homologues ofSaccharomyces cerevisiae Spt3 suggest conserved functional domains

Abstract: Spt3 of Saccharomyces cerevisiae is a factor required for normal transcription from particular RNA polymerase II-dependent promoters. As a step towards analysing Spt3 structure-function relationships, we have identified and studied Spt3 homologues from three other yeasts: Kluyveromyces lactis, Clavispora opuntiae and Schizosaccharomyces pombe. Alignment of their predicted amino acid sequences shows an overall identity of 30% between all four homologues and suggests that three conserved domains are present in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition, microarray analyses have shown that Gcn5 is involved in the regulation of a subset of genes induced during salt stress (Johnsson et al 2006). Other S. pombe orthologs of S. cerevisiae SAGA components have also been identified by sequence homology, including Spt3 (Madison and Winston 1998), Taf5 (Yamamoto et al 1997;Mitsuzawa et al 2001), Taf6 (Mitsuzawa and Ishihama 2002), and Tra1 (Hayashi et al 2007). Finally, sep9 + , which was identified in a screen for genes required for cytokinesis and sexual differentiation, was suggested to be the ortholog of S. cerevisiae SPT8 .…”
mentioning
confidence: 99%
“…In addition, microarray analyses have shown that Gcn5 is involved in the regulation of a subset of genes induced during salt stress (Johnsson et al 2006). Other S. pombe orthologs of S. cerevisiae SAGA components have also been identified by sequence homology, including Spt3 (Madison and Winston 1998), Taf5 (Yamamoto et al 1997;Mitsuzawa et al 2001), Taf6 (Mitsuzawa and Ishihama 2002), and Tra1 (Hayashi et al 2007). Finally, sep9 + , which was identified in a screen for genes required for cytokinesis and sexual differentiation, was suggested to be the ortholog of S. cerevisiae SPT8 .…”
mentioning
confidence: 99%
“…We next analyzed the roles of Spt3p and Spt8p in the recruitment of TBP to SAGAdependent promoters. Spt3p is a functionally conserved eukaryotic transcriptional regulator (29,41) believed to play roles in both the activation and repression of transcription (4,26,40). Genetic and biochemical studies have shown that Spt3p interacts with TBP (13,14,27).…”
mentioning
confidence: 99%